Inclusive Cities for All Beings: Urban Animal Governance From a “One Welfare” Perspective - De Ruyver, Ciska (2026)
Urban environments are predominantly designed and governed from a human‐centred perspective, largely overlooking the experiences and welfare of animals. Yet cities are shared spaces in which animals live in environments profoundly shaped by human activity. Because of global urbanisation, interspecies interactions will intensify, becoming more frequent and complex. This development raises pressing questions about the welfare of animals in urban contexts and the human responsibility for these animals. While humans hold direct responsibility for domestic animals under their care, such as cats and dogs, we argue that they also bear indirect obligations toward commensal species, such as rats, foxes, and pigeons, whose lives depend on human‐modified habitats. Situating urban animal welfare alongside human wellbeing aligns with the One Welfare framework, which recognises the interdependence of human, animal, and environmental welfare. In contrast to narrower One Health approaches that primarily focus on health risks and biosecurity, One Welfare foregrounds welfare and relationality across species. This article argues that animal welfare should be understood as a constitutive element of urban governance rather than a secondary concern. Drawing on illustrative examples from Belgian cities, the study demonstrates that, to date, animal welfare considerations remain insufficiently integrated into urban governance practices. Therefore, we call for the systematic integration of scientific animal welfare knowledge into urban governance to advance animal welfare. Building on the One Welfare framework, the article advances the concept of “multispecies cities” as part of a broader vision of compassionate urban futures grounded in care and coexistence between humans and animals.